Defining the identity of mouse embryonic dermal fibroblasts. Issue 8 (24th June 2016) - Budnick, Isadore; Hamburg‐Shields, Emily; Chen, Demeng; Torre, Eduardo; Jarrell, Andrew; Akhtar‐Zaidi, Batool; Cordovan, Olivia; Spitale, Rob C.; Scacheri, Peter; Atit, Radhika P.
Summary: Embryonic dermal fibroblasts in the skin have the exceptional ability to initiate hair follicle morphogenesis and contribute to scarless wound healing. Activation of the Wnt signaling pathway is critical for dermal fibroblast fate selection and hair follicle induction. In humans, mutations in Wnt pathway components and target genes lead to congenital focal dermal hypoplasias with diminished hair. The gene expression signature of embryonic dermal fibroblasts during differentiation and its dependence on Wnt signaling is unknown. Here we applied Shannon entropy analysis to identify the gene expression signature of mouse embryonic dermal fibroblasts. We used available human DNase‐seq and histone modification ChiP‐seq data on various cell‐types to demonstrate that genes in the fibroblast cell identity signature can be epigenetically repressed in other cell‐types. We found a subset of the signature genes whose expression is dependent on Wnt/β‐catenin activity in vivo . With our approach, we have defined and validated a statistically derived gene expression signature that may mediate dermal fibroblast identity and function in development and disease. genesis 54:415–430, 2016. © 2016 Wiley Periodicals, Inc.